ANALISA HUBUNGAN NILAI PERUBAHAN CHEMICAL OXYGEN DEMAND (COD) DAN pH PADA PALM OIL MILL EFFLUENT (POME) DALAM PROSES PEMBUATAN BIOGAS - Hafiz, Muhammad; Purwanto, Heri; Rahimah; Giyanto (Institut Teknologi Sawit Indonesia (ITSI), 2024)
Palm Oil Mill Effluent (POME) is abundantly available in the palm oil industry and has significant potential for generating renewable energy, specifically biogas, through the biogasification process. This study investigates the relationship between the reduction of Chemical Oxygen Demand (COD) values and pH changes in POME during the biogas production process. The study employs a Completely Randomized Design (CRD) with a single factor and four levels. Data were analyzed over five observation periods spanning 24 days. The results show a significant decrease in COD concentration from 96,300 mg/L on day 0 to 22,720 mg/L on day 24. This reduction is attributed to microbial activity, with Effective Microorganisms (EM4) being used in this research. Additionally, an inverse relationship between pH and COD was observed, where an increase in pH correlated with a decrease in COD. Biogas production also increased over time, with the cumulative biogas volume reaching 5.2 liters on day 24. The study concludes that more alkaline environmental conditions support the activity of microorganisms responsible for COD reduction and higher biogas production. Recommendations for future research include adding parameters such as temperature and Volatile Fatty Acids (VFA), and further investigation into more effective and efficient microorganism seeding. Thus, this research provides insights into the biogasification process and the development of more efficient and sustainable biogas technology.